A New Approach to the Life and Oeuvre of Karl Leonhard: His Role as a Psychiatrist under National Socialism and the Influence of "Erlangen School" on his Scientific Position - Braun, Birgit; Kornhuber, Johannes (Fortschritte der Neurologie - Psychiatrie, 2022)
Aim The aim of this study was to present a new approach to the life and oeuvre of Karl Leonhard, focussing on his role as a psychiatrist during the period of national socialism and on his scientific affiliation to the "Erlangen school". Method For the first time, documents from Franconian archives have been evaluated. Results At the University Hospital of Psychiatry in Erlangen, Leonhard described psychopathological states in a very detailed manner as a main component of his phenomenological approach. Although Leonhard was classified as a "follower" during his denazification, temporarily he was "incriminated" due to a denunciation. Conclusion Leonhard as an opportunist supported the NS racial hygiene without any actual eugenic orientation. Further studies are needed to clarify Leonhard's proclaimed active opposition to NS "euthanasia".
CRIS-Team WoS Importer:2022-04-22